Surface wind variability on seasonal and interannual scales over RíO de la Plata area - Simionato, Claudia Gloria (2005)
Previous works show that wind forcing is the main source of circulation seasonal variability in the Río de la Plata estuary, located on the southeastern coast of South America. Wind forcing exceeds by far the role of fresh water discharges. However, due to a lack of enough observations, the features and causes of surface wind variability are not well understood yet. Therefore this paper presents a comprehensive study of surface wind variability over the Río de la Plata estuary using the National Center for Environmental Prediction-National Center for Atmospheric Research (NCEP/NCAR) reanalysis data between 1948 and 1997. It is expected that this study contributes to better understand, model and thus predict the estuary circulation. An onshore to offshore rotation characterizes the seasonal variations of the surface winds from summer to winter. A linear trend analysis shows a displacement of the summer-winter seasonal features to earlier months. On interannual time-scales, the first leading pattern describes east-west changes of surface winds that seems to be forced by the quasibiennial tropospheric oscillation excited in the western tropical Pacific and previously identified by many authors. The conditions over the South Atlantic and in particular the Río de la Plata are influenced by such oscillation through an atmospheric Rossby wave train propagating out of the tropics. This result is very important for its implication on the predictability levels in the region. The second leading mode is associated with anticyclonic/cyclonic wind rotations off the estuary on interannual times scales which are related with changes in both atmospheric and oceanic surface conditions at Southern Hemispher high-latitudes.